Social mobilization, global capitalism and struggles over food: a comparative study of social movements - Campos Motta, Renata (Routledge, 2016)
1. Theorizing and research disputes over GMOs -- 2. A silenced revolution (1996-2002) -- 3. Increasing noise (2003-2013) -- 4. The unexpectedly contentious Brazilians (1996-2002) -- 5. The politics of fait accomplis (2003-2013) -- 6. Many tales of GMOs : a comparison -- 7. Conclusions.
Includes bibliographical references (pages [164]-183) and index
Keywords: Brasilien; Argentinien; Soziale Bewegung; Ökologische Bewegung; Kapitalismus; Globalisierung; Gentechnisch verändertes Lebensmittel; Agrarpolitik